TELLURIUM AND THALLIUM IN FERROMANGANESE CRUSTS AND PHOSPHATES ON OCEANIC SEAMOUNTS - Baturin G.N. (My University, 2007)
Tellurium and thallium are among the least widespread elements in the Earth. Their contents in the Earth’s crust, in general, and igneous and sedimentary (including oceanic) rocks, in particular, vary from <1 to n mg/t. These metals attract special attention from geologists and geochemists because of their very high (four orders of magnitude or more) concentrations in some rocks. In oceans, such rocks are represented by ferromanganese crusts (hereafter, crusts) that make up extended sheets on the surface of many seamounts with summits located at a depth of more than 1–2 km.